A Pre-Hospital Extracorporeal Cardio Pulmonary Resuscitation (ECPR) strategy for treatment of refractory out hospital cardiac arrest: An observational study and propensity analysis. (August 2017) - Lamhaut, Lionel; Hutin, Alice; Puymirat, Etienne; Jouan, Jérome; Raphalen, Jean-Herlé; Jouffroy, Romain; Jaffry, Murielle; Dagron, Christelle; An, Kim; Dumas, Florence; Marijon, Eloi; Bougouin, Wulfran; et al.
Abstract: Background: Out of hospital cardiac arrest (OHCA) mortality rates remain very high with poor neurological outcome in survivors. Extracorporeal cardiopulmonary resuscitation (ECPR) is one of the treatments of refractory OHCA. This study used data from the mobile intensive care unit (MOICU) as part of the emergency medical system of Paris, and included all consecutive patients treated with ECPR (including pre-hospital ECPR) from 2011 to 2015 for the treatment of refractory OHCA, comparing two historical ECPR management strategies. Methods: We consecutively included refractory OHCA patients. In Period 1, ECPR was indicated in selected patients after 30 min of advanced life support; in- or pre-hospital implementation depended on estimated transportation time and ECPR team availability. In Period 2, patient care relied on early ECPR initiation after 20 min of resuscitation, stringent patient selection, epinephrine dose limitation and deployment of ECPR team with initial response team. Primary outcome was survival with good neurological function Cerebral Performance Category score (CPC score) 1 and 2 at ICU discharge or day 28. Findings: A total of 156 patients were included. (114 in Period 1 and 42 in Period 2). Baseline characteristics were similar. Mean low-flow duration was shorter by 20 min (p < 0.001) in Period 2. Survival was significantly higher in Period 2: 29% vs 8% (P < 0.001), as confirmed by the multivariate analysis and propensity score. When combining stringent patient selection with an aggressive strategy, the survival rate increased to 38%. Pre-hospital ECPR implementation in itself was not an independent predictor of improved survival, but it was part of the strategy in Period 2. Interpretation: Our data suggest that ECPR in specific settings in the management of refractory OHCA is feasible and can lead to a significant increase in neurological intact survivors. These data, however, need to be confirmed by a large RCT.